MENINGKATKAN MINAT MEMBACA MELALUI METODE GLENN DOMAN BERBANTUAN MEDIA FLASHCARD PADA SISWA KELAS I SD - Mita Sawitri; Maryono Maryono; Silvina Noviyanti (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This study aims to determine the process of applying the Flashcard Media-Based Glenn Doman method in increasing Reading Interest of Class I Students at SDN 134/I Merbau. This type of research is classroom action research. The research data was obtained from observation. Then the data were analyzed qualitatively by describing the increase in students' reading interest using flashcard media and quantitatively in the form of students' reading interest scores. Based on the research results, the application of the Glenn Doman method based on flashcard media was able to increase students' interest in reading. This is because students experience an increase in reading interest by paying attention to each indicator of reading interest in their learning which can be seen in each cycle. In the cycle I know that the level of interest in reading students is in the